Mutations and copy number alterations in diffuse gliomas are shaped by different mechanisms - Ozduman, K.; Ulgen, E.; Karacan, S.; Gerlevik, U.; Can, O.; Bilguvar, K.; Akyerli, C. B.; Yuksel, S. K.; Ersen\\-Danyeli, A.; Tihan, T.; Yakicier, C.; Sezerman, O. U.; et al. (ELSEVIER SCI LTD, 2020)
32nd EORTC-NCI-AACR Symposium on Molecular Targets and Cancer Therapeutics, ELECTR NETWORK, OCT 24-25, 2020